Health-related quality of life and its influencing factors in patients with primary cutaneous B-cell lymphomas: a multicentric study in 100 patients - Schirren, Anne Ellen Christiane; Albrecht, Jana Dorothea; Melchers, Susanne; Weiß, Christel; Büttner, Sylvia; Dippel, E.; Gosmann, J.; Jonak, C.; Klemke, Claus-Detlev; Laturnus-Chang, M.; Livingstone, E.; Mitteldorf, C.; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
Background Primary cutaneous B-cell lymphomas (CBCL) are a group of rare malignant skin diseases that represent approximately 20%-30% of all primary cutaneous lymphomas (PCL). Previous studies revealed impaired health-related quality of life (HRQoL) in patients diagnosed with primary cutaneous T-cell lymphoma (CTCL). Currently, only small-sized studies investigated HRQoL in CBCL patients and lacked detailed analysis of respective subtypes. Objectives This study aims to investigate HRQoL in CBCL patients to identify independent factors of HRQoL impairment in CBCL patients. Methods One hundred CBCL patients were recruited from eight German PCL centres in this multicentric, cross-sectional study from 2021 to 2022. The patients completed the dermatologic HRQoL questionnaire Skindex-29 and an investigator-designed ‘CBCL-Questionnaire’ with additional questions on HRQoL and clinical characteristics. Results The Skindex-29 revealed that HRQoL in CBCL patients is impaired on a mild to moderate level. The multiple regression analysis identified parameters like worries about dying, feeling prejudiced/discriminated and impairment of daily activities to be independently associated with impairment of HRQoL. Highest scores for HRQoL impairment were found in patients with primary cutaneous follicle centre lymphoma while on rituximab treatment and in patients with primary cutaneous marginal zone lymphoma while on watchful waiting. Conclusions HRQoL is impaired in CBCL patients, even though, in the face of indolent disease course and favourable prognosis in the majority of cases. Of note, our investigator-designed tool identified worries about dying, feeling prejudiced/discriminated, and the type of treatment to have a negative impact on patients' HRQoL. Our study highlights the importance of a thorough patient-doctor communication to capture overall disease burden because generic HRQoL tools might lack of disease-specific items.
Online veröffentlicht: 26. Januar 2024
Gesehen am 19.12.2024